High-throughput measurement of human platelet aggregation under flow: application in hemostasis and beyond. (3rd October 2018) - Brouns, Sanne L. N.; van Geffen, Johanna P.; Heemskerk, Johan W. M.
Abstract: In recent years, considerable progress has been made in understanding the mechanisms involved in platelet activation during hemostasis and thrombosis. Parallel-plate flow chambers and other microfluidic devices have markedly contributed to this insight. Conversely, such flow devices are now increasingly used to monitor the combined processes of platelet aggregation, thrombus formation, and coagulation in human blood. Currently, by combining microspotting and multi-color fluorescence microscopy, this technology offers the capability of high-throughput measurement of platelet activation processes, even in small blood samples. Here we review the potential of flow chamber devices for complex (multiparameter) platelet and coagulation phenotyping, focusing on patients with (genetic) platelet- or coagulation-based bleeding disorders as well as monitoring of antithrombotic medication. Animal studies are not discussed.